Analysis of Interactive Multimedia Needs for Mathematics Subjects at Madrasah Ibtidaiyah Al-Hunafa Palangka Raya - Gusti Nida Nurkhaliza; Fathul Zannah; Tazkiyatunnafs Elhawwa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Mathematics is a subject that almost all students consider to be difficult, boring, and unpleasant. Teachers are essential in packaging learning and using engaging media to make learning fun and memorable. Aim: This research analyzes the need for interactive multimedia and student learning outcomes. Method: This research uses a qualitative approach, with a qualitative descriptive method, for data collection techniques carried out using teacher and student interview instrument sheets, direct observation, and distributing interactive multimedia needs questionnaires. Results and Dıscussion: The results of the need for interactive multimedia (indicator 1 of the causes of low mathematics learning outcomes) show that 56% (14 out of 25 students) think mathematics is too complicated. For (Indicator 2 methods that teachers often use), the results showed that 64% (16 of 25 students) answered that the teacher explained the lesson and gave practice questions. For (Indicator 3, the impression of mathematics learning), 48% (12 of 25 students) thought that mathematics is a tough lesson, 24% (6 out of 25 students) said it was boring, 20% (5 out of 25 students) said it was challenging but fun and 8% (2 out of 25 students) said learning mathematics made them curious. In (indicator 4, Frequently used learning resources) there were 56% (14 out of 25 students) stated that worksheets were the primary learning source, and 44% (11 out of 25 students) answered textbooks. Conclusion: This research concludes that students need new learning resources such as interactive multimedia in speed and discharge subjects, indicating that 100% of students support and need this media in learning.